93.6k views
4 votes
Solve for y.

y – (–19) = 25


A.
–44

B.
–6

C.
6

D.
44

2 Answers

5 votes

Answer:

Answer is C. 6

Explanation:

Because:

y -(-19) = 25 (well i always put a 1 infront of parenthesis) so,

y -1(-19) =25 distribute the 1 in the parenthesis and you would get

19=25 minus 19 on both sides and you get y= 6

Hope my answer has helped you!

User Trastle
by
5.8k points
4 votes

Answer:

C

Explanation:

note that - (- 19) = + 19

Given

y - (- 19) = 25, that is

y + 19 = 25 ( subtract 19 from both sides )

y = 6 → C

User Dader
by
6.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.